Burnout syndrome among medical nurse-technicians in intensive care units in cardiovascular surgery - Nenadovic, Aleksandar; Radovanovic, Snezana; Joksimovic, Stefan; Gavrilovic, Jagoda; Sorak, Marija; Spasic, Marko; Djonovic, Nela; Vasiljevic, Dragan; Stajic, Dalibor; Djordjevic, Gordana; Djordjevic, Ognjen; Vuckovic-Filipovic, Jelena; et al. (Frontiers in Public Health, 2023)
Background: Healthcare workers in intensive care units work under specifically hard conditions compared to healthcare workers who work under regular clinical conditions. In this sense, the research aims at assessing the level of burnout symptomatology among nurse technicians working in intensive care units for cardiovascular surgery and to compare those burnout levels with those recorded for medical technicians working under regular clinical conditions.: The research was designed as a cross-sectional study. The sample consisted of nurse technicians working in intensive care units specializing in cardiovascular surgery (70 participants) and nurse technicians working under regular clinical conditions (70 participants) at the Institute for Cardiovascular Diseases "Dedinje," Belgrade, Serbia. To evaluate the manifestation of burnout syndrome at work, the analysis uses the Serbian version of the Maslach Burnout Inventory-Human Services Survey (MBI-HSS).Results: To examine the variances in the average sub-scores for burnout within two groups of medical technicians, the study used Two Independent Samples T-test. The statistically noteworthy differentiation was ascertained for emotional exhaustion and personal accomplishment, but this does not hold true for depersonalization. However, the mean score values across the different burnout levels (low, moderate, high) are similar in two cohorts of respondents (p > 0.05).This study will serve as an impetus for a policy reform focused on ameliorating working conditions and improving healthcare workers' satisfaction and overall healthcare quality.